Psycho-physiological markers of overreaching and overtraining in endurance sports: A review of the evidence - Bell, L. M.; Ingle, L. (Medicina Sportiva, 2013)
We review the latest evidence from studies that have examined psycho-physiological markers of overreaching (OR) and overtraining (OT) in endurance-based sports. MEDLINE (PubMed), SportDiscus©, AdisOnline and Ingentaconnect© were searched without time or language restrictions using free text words. Hand searching was conducted, with searches supplemented by a review of the bibliography of each retrieved article. There were 152 studies identified and associated with OR/OT in the context of endurance-based exercise. Collectively, a multitude of psycho-physiological markers have been implicated in their relationship with OR/OT in swimming, cycling and running activities. There is no single marker that can be used to identify OR/OT, and we discuss problems associated with the identification of OT. We also discuss prevalence, symptoms, diagnosis of OR/OT, and provide recommendations to coaches and athletes.